2010 18th IEEE International Requirements Engineering Conference 2010
DOI: 10.1109/re.2010.26
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Preferences into Goal Models for Requirements Engineering

Abstract: Abstract-Requirements can differ in their importance. As such the priorities that stakeholders associate with requirements may vary from stakeholder to stakeholder and from one situation to the next. Differing priorities, in turn, imply different design decisions for the end system. While elicitation of requirements priorities is a well studied activity, though, the modeling and reasoning side of prioritization has not enjoyed equal attention. In this paper, we address this by extending a traditional goal mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 23 publications
0
45
0
Order By: Relevance
“…Thus we can apply it to the other modeling techniques where make requirement dependency explicitly represented, such as the order of tasks [20]. Showing its wide applicability is one of the future issues.…”
Section: Discussionmentioning
confidence: 99%
“…Thus we can apply it to the other modeling techniques where make requirement dependency explicitly represented, such as the order of tasks [20]. Showing its wide applicability is one of the future issues.…”
Section: Discussionmentioning
confidence: 99%
“…Goal modeling has been used extensively in the context of early requirements engineering for software design [55,82] to express stakeholder goals at different levels of abstraction and to show the impact of different software design alternatives on these goals. This includes work on acquiring such variability [45], selecting alternatives based on user skills and preferences [36], using goalmodels to reason about software configurations [45] as well as incorporating end-user preferences [47]. A variety of techniques for performing automated reasoning about such goal models have been proposed [29,35,71].…”
Section: Related Workmentioning
confidence: 99%
“…A variety of techniques for performing automated reasoning about such goal models have been proposed [29,35,71]. Some of these, e.g., [13,30,85], use planners -the reasoning framework we adopt in our work [47,75]. Planner-based approaches have the benefit of distinguishing between preferences and mandatory goals.…”
Section: Related Workmentioning
confidence: 99%
“…Each course selection will be checked by examination rules, and only students who have their course registration fees successfully paid will be accepted by the system. This kind of timing constraints is a prerequisite for the execution of relevant tasks, and can be modelled by precedence links (Liaskos et al, 2010). A deviation of such timing constraints can be regarded as a potential failure, which can be handled by self-repairing mechanisms.…”
Section: A Running Example and Its Requirements Modelmentioning
confidence: 99%
“…Our experiment also showed that an interval of 0.1 was sufficient for the example driven by relatively small number of quality requirements. Recently, a HTN (Hierarchical Task Networks) preference-based planer is used to efficiently search for alternatives that best satisfy the given preferences (Liaskos et al, 2010), which can in future be integrated into our framework to provide more efficient goal reasoning.…”
Section: Related Workmentioning
confidence: 99%